Experimental Study and DEM Simulation of Size Effects on the Dry Density of Rockfill Material - Zhao, Xiaolong; Zhu, Jungao; Wu, Yunlong; Jia, Yun; Bur, Nicolas; Colliat, Jean-Baptiste; Bian, Hanbing (Frontiers in Physics, 2022)
The initial dry density has a significant effect on the mechanical behavior of rockfill material (RFM). The size effects on the minimum/maximum dry density (referred to as dry density, ρd) of RFM still need further study. To investigate the relationship between ρd and dM, a series of surface vibration compaction tests and DEM simulations are performed on the samples with different maximum particle sizes dM. Both the physical and numerical results exhibit that ρd increases fast when dM ranges from 10 to 40 mm. When dM exceeds 40 mm, ρd increases slowly and tends to be a constant. Results indicate that ρd is affected by the gradation. To consider the gradation effect, a normalized parameter λ is introduced, and the relation between ρd and dM can be characterized by an empirical equation.